Long-term safety and efficacy of deferasirox (Exjade®) for up to 5 years in transfusional iron-overloaded patients with sickle cell disease - Vichinsky, Elliott (Blackwell Publishing Ltd, 2011)
To date, there is a lack of long-term safety and efficacy data for iron chelation therapy in transfusion-dependent patients with sickle cell disease (SCD). To evaluate the long-term safety and efficacy of deferasirox (a once-daily oral iron chelator), patients with SCD completing a 1-year, Phase II, randomized, deferoxamine (DFO)-controlled study entered a 4-year extension, continuing to receive deferasirox, or switching from DFO to deferasirox. Average actual deferasirox dose was 19·4 ± 6·3 mg/kg per d. Of 185 patients who received at least one deferasirox dose, 33·5% completed the 5-year study. The most common reasons for discontinuation were withdrawal of consent (23·8%), lost to follow-up (9·2%) and adverse events (AEs) (7·6%). Investigator-assessed drug-related AEs were predominantly gastrointestinal [including nausea (14·6%), diarrhoea (10·8%)], mild-to-moderate and transient in nature. Creatinine clearance remained within the normal range throughout the study. Despite conservative initial dosing, serum ferritin levels in patients with ≥4 years deferasirox exposure significantly decreased by −591 μg/l (95% confidence intervals, −1411, −280 μg/l; P=0·027; n=67). Long-term deferasirox treatment for up to 5 years had a clinically acceptable safety profile, including maintenance of normal renal function, in patients with SCD. Iron burden was substantially reduced with appropriate dosing in patients treated for at least 4 years.